1993
DOI: 10.1210/endo.132.3.7679981
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of human chorionic gonadotropin in differentiation of human cytotrophoblasts.

Abstract: Our laboratory previously demonstrated that cytotrophoblasts and syncytiotrophoblasts in human placental tissue contain hCG/LH receptors. From this finding, we postulated that one role of hCG might be to promote the differentiation of cytotrophoblasts into syncytiotrophoblasts. To test this postulate, cytotrophoblasts were isolated from human term pregnancy placentas and cultured with and without increasing concentrations of highly purified hCG. The results showed that hCG had a biphasic effect on 1) the aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(49 citation statements)
references
References 0 publications
1
47
0
1
Order By: Relevance
“…In a second step, we analyzed whether CTB and STB exhibit physiological features similar to in vivo conditions [31,32,33]. Therefore, we compared the gene expression and secretion of human chorionic gonadotropin ( hCG ), human placental lactogen ( hPL ), and endoglin between CTB and STB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second step, we analyzed whether CTB and STB exhibit physiological features similar to in vivo conditions [31,32,33]. Therefore, we compared the gene expression and secretion of human chorionic gonadotropin ( hCG ), human placental lactogen ( hPL ), and endoglin between CTB and STB.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we compared the gene expression and secretion of human chorionic gonadotropin ( hCG ), human placental lactogen ( hPL ), and endoglin between CTB and STB. The abundances of hCG and hPL were determined because it has been demonstrated that the expression of these genes increases with trophoblast differentiation and syncytium formation [31,33]. Endoglin is strongly expressed on the apical membrane of STB with a possible role in syncytial invasiveness and angiogenesis [32,34].…”
Section: Resultsmentioning
confidence: 99%
“…Some embryonic signals modulating this dialogue have been identified 7–9 . Among them, human chorionic gonadotrophin synthesized early by the trophoblast cells acts on the uterine environment via the luteinizing hormone/hCG receptor and exerts both autocrine effects, promoting differentiation 10 and migration of trophoblasts 11 , and paracrine effects on the maternal endometrium 12 . Another molecule identified in embryo culture media and supposed to be involved in the regulation of local maternal immune response is represented by sHLA-G 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The observation that CTBs and the STB layer express hCG and its receptor suggests that hCG may impose an autocrine and/or a paracrine effect on trophoblastic differentiation through cAMP and PKA (12). Shi et al (13) showed that inhibition of PKA by H89 blocks hCG-induced trophoblastic differentiation.…”
mentioning
confidence: 99%